Nano-catalysts for upgrading bio-oil: Catalytic decarboxylation and hydrodeoxygenation - Uemura, Y. (American Institute of Physics Inc., 2017)
Bio-oil is a mixture of oxygenated chemicals produced by fast pyrolysis of lignocellulose, and has attracted much attention recently because the raw material is renewable. Primarily, bio-oil can be used as a replacement of heavy oil. But it is not highly recommended due to bio-oil's inferior properties: high acidity and short shelf life. Upgrading of bio-oil is therefore one of the important technologies nowadays, and is categorized into the two: (A) decrarboxylation/decarbonylation by solid acid catalysts and (B) hydrodeoxygenation (HDO) by metallic catalysts. In our research group, decarboxylation of bio-oil by zeolites and HDO of guaiacol (a model compound of bio-oil) have been investigated. In this paper, recent developments of these upgrading reactions in our research group will be introduced. © 2017 Author(s).